Current status and future operational models for transit shipping along the Northern Sea Route. (August 2018) - Milaković, Aleksandar-Saša; Gunnarsson, Bjørn; Balmasov, Sergey; Hong, Sungwon; Kim, Kitae; Schütz, Peter; Ehlers, Sören
Abstract: The Northern Sea Route (NSR) has received increased international attention during the recent years as an alternative transit corridor for shipping between Europe and East Asia. In 2015, the project "Feasibility and Reliability of Shipping on the Northern Sea Route and Modeling of an Arctic Marine Transportation & Logistics System" was established to perform a comprehensive analysis of the current status and future prospects of NSR transit shipping. The project brought together several partners and numerous participants representing industry, governmental bodies, and research groups from Europe, Asia, and Russia, thus providing a unique and comprehensive overview of the subject. This paper is based on the insights gathered during the project. Firstly, it provides a comprehensive overview of the NSR's current regulations and support services. Secondly, it combines the information on the current status of the route with feedback received from the stakeholders during project discussions for the purpose of establishing several possible future operational models for transit shipping along the NSR. It is concluded that the most probable of the analyzed operational models is a combination of ice-strengthened vessels and independent ice-going cargo vessels. This model requires a decrease in severity of ice conditions to allow for year-round commercial navigation, an increase in bunker prices, further development of maritime infrastructure and icebreaking support, and the development of new maritime insurance models. Additionally, establishing transshipment hubs at each end of the NSR with ice-going cargo vessels sailing between them is also considered to be a viable future option. Highlights: Comprehensive overview of current status of the NSR is given. Stakeholders' perspectives on NSR transit shipping are presented. Future operational models for NSR transit shipping are developed and analyzed. Assisted ice-strengthened and independent ice-going vessels are most probable. Ice conditions, bunker prices, infrastructure and insurance are decisive factors.